Penile beads and its associated infections: a descriptive study - Halder, Ram Kanta; Balasubramanian, Pradeep (International Journal of Research in Dermatology, 2019)
Background: Practice of introducing glass beads in the penis has been done amongst the poachers from the neighboring countries of Andaman and Nicobar Islands, e. g. Myanmar, Thailand and Indonesia to improve their sexual performance. Methods: Patients attending the skin OPD, G.B. Pant Hospital and the poachers in the District Hospital, Pothrapur with beads and foreign body introduced in the penis were included in this study. Results: Totally 41 patients were enrolled in this study. All the patients were poachers (from Myanmar and Thailand). About 90% had inserted glass beads into the prepuce and 10% had injected oil. About 17% and 36.58% of these poachers were suffering from HIV infection and other sexually transmitted infections respectively. About 19.5% of the poachers had syphilis. Conclusions: It is observed that this peculiar sexual habit or behavior cause increased incidence of sexually transmitted diseases and AIDS in these poachers and hence it is a risky practice.